STUDENTS RESPONSES IN LEARNING READING USING WHATSAPP - Firanti, Ransha Faliska; Efransyah, Efransyah (IKIP Siliwangi, 2024)
Nowadays, the use of mobile devise not only to communicate but also to learn, to share information, to support teaching and learning especially after pandemic covid-19. As it is implemented by educators, on its process, it has hinger challenges to attract students’ attention and interest during the online learning. This study entitled Students’ Responses in learning reading using WhatsApp aims to identify the students' responses on the online learning through WhatsApp. The method used in this research is qualitative research method, while the subjects consist of 34 students. The obtained data from a questionnaire with an average percentage of 45.9%. It illustrated that the students felt that learning using Asynchronous could decrease learning enthusiasm due to a natural lack of interaction with the social environment.